The Raphe Pallidus and the Hypothalamic-Pituitary-Thyroid Axis Gate Seasonal Changes in Thermoregulation in the Hibernating Arctic Ground Squirrel (Urocitellus parryii) - Frare, Carla; Jenkins, Mackenzie E.; Soldin, Steven J.; Drew, Kelly L. (Frontiers in Physiology, 2018)
Thermoregulation is necessary to maintain energy homeostasis. The novel discovery of brown adipose tissue (BAT) in humans has increased research interests in better understanding BAT thermogenesis to restore energy balance in metabolic disorders. The hibernating Arctic Ground Squirrel (AGS) offers a novel approach to investigate BAT thermogenesis. AGS seasonally increase their BAT mass to increase the ability to generate heat during interbout arousals. The mechanisms promoting the seasonal changes in BAT thermogenesis are not well understood. BAT thermogenesis is regulated by the raphe pallidus (rPA) and by thyroid hormones produced by the hypothalamic-pituitary-thyroid (HPT) axis. Here we investigate if the HPT axis and the rPA undergo seasonal changes to modulated BAT thermogenesis in hibernation. We used histological analysis and tandem mass spectrometry to assess activation of the HPT axis and immunohistochemistry to measure neuronal activation. We found an increase in HPT axis activation in fall and in response to pharmacologically-induced torpor when adenosine A1 receptor agonist was administered in winter. By contrast, the rPA neuronal activation was lower in winter in response to pharmacologically induced torpor. Activation of the rPA was also lower in winter compared to the other seasons.Our results suggest that thermogenic capacity develops during fall as the HPT axis is activated to reach maximum capacity in winter seen by increased free thyroid hormones in response to cooling. However thermogenesis is inhibited during torpor as sympathetic premotor neuronal activation is lower in winter, until arousal when inhibition of thermogenesis is relieved. These findings describe seasonal modulation of thermoregulation that conserves energy through attenuated sympathetic drive, but retains heat generating capacity through activation of the HPT axis.